Gamified Mobile Learning: EFL Students’ Attitudes Toward Quizizz for Grammar Instruction - Pham, Duc Thuan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study explores Vietnamese English as a Foreign Language (EFL) students’ attitudes toward the application of Quizizz as a mobile-assisted language learning (MALL) tool for grammar instruction. With the increasing integration of gamified platforms in language education, understanding students’ perceptions and engagement with such tools is essential. The study employs a quantitative research design, collecting data from 102 students enrolled in a general English course at a university in northern Vietnam. Using a questionnaire, students’ attitudes were examined across affective, behavioral, and cognitive dimensions, along with their level of satisfaction with Quizizz. The findings indicate that students generally hold highly positive attitudes toward Quizizz, with high mean scores in affective (M = 4.4828, SD = 0.70383), behavioral (M = 4.3652, SD = 0.60594), and cognitive (M = 4.5025, SD = 0.61690) dimensions, highlighting strong emotional engagement, motivation, and perceived usefulness. A significant positive correlation between attitudes and satisfaction (r = .861, p < .01) underscores the effectiveness of Quizizz in fostering an engaging learning experience. However, an analysis of gender differences revealed no statistically significant variations in attitudes, suggesting that both male and female students perceive the platform similarly. The study concludes that Quizizz is a valuable tool for grammar learning, reinforcing motivation, engagement, and satisfaction. Findings contribute to theoretical discussions on MALL and gamification, offering practical implications for EFL educators seeking to integrate technology effectively into grammar instruction.